Penafsiran Ayat-Ayat Tentang Korupsi - Naili Amalia; Rahmi Syafitri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Corruption is an issue that has received attention in the Qur'an, although it has not been studied in depth in terms of legal aspects and scientific research. Some verses of the Qur'an contain concepts related to corruption, but have not yet become the main reference in Islamic legal studies. This study aims to reveal the meaning of corruption in the Qur'an through the analysis of relevant verses and the interpretations of the mufassirs in various books of interpretation. The focus of this study is to explore the Qur'anic perspective on corrupt practices by referring to the interpretations of the scholars of tafsir. In the Qur'an, some terms that approach the meaning of corruption include robbery (hirabah), theft (as-sariqah), treason (al-ghulul), and bribery (as-suht).